Maritime Intelligence in Countering Destructive Fishing as a Threat to Maritime Security in Coastal Areas and Small Islands - Dao, Yunias; Yusnaldi, Yusnaldi; Kusuma, Kusuma (Faculty of Social Science, Universitas Negeri Padang, 2024)
Destructive fishing has been identified as a major threat to maritime security, particularly in coastal areas and small islands. This practice, as a form of illegal fishing, results in adverse economic impacts, damage to ecosystems, threats to resource sustainability, and impacts on national security. This research aims to examine the role of maritime intelligence in overcoming destructive fishing as a maritime security threat in coastal areas and small islands in Indonesia. The method used in this research is qualitative, with a comprehensive literature review and case study approach. This research integrates national security theory, maritime security theory, intelligence role theory and literature study to analyze the data. The results show that maritime intelligence plays an important role in identifying and intervening in destructive fishing practices. This role includes early detection and response to illegal activities, as well as the generation of more effective prevention and mitigation measures. The conclusion of this study confirms that optimizing the role of maritime intelligence can improve the effectiveness of monitoring and countering destructive fishing, thereby reducing negative impacts on the economy, ecosystems and national security. Recommendations from this study include improving the implementation and coordination of maritime intelligence and involving local communities in monitoring to increase the effectiveness and efficiency of destructive fishing prevention and mitigation efforts.